Opportunities and challenges of supply chain sustainability reporting - Juhart, Sergeja (Naše gospodarstvo, 2025)
This article explores reporting on supply chain sustainability from the perspective of opportunities and challenges for multinational manufacturing companies, considering the evolved European Union (EU) regulations and the scope and complexity of international supply chains. In the theoretical part, we examine corporate sustainability reporting, focusing on EU regulatory framework, sustainability in international supply chain management, and reporting on supply chain sustainability. The empirical analysis is based on the secondary and primary data gathered from a non-random sample of Slovenian multinational manufacturing companies from B2B industry. The analysis shows that the companies discussed included information on supply chain sustainability in their sustainability reports; however, they weren't very well-prepared for the requirements of the new EU sustainability reporting directives. We found they perceived opportunities and challenges in supply chain sustainability reporting similarly. Our research findings have several implications for corporate sustainability management and national institutional business support.
Keywords: corporate sustainability; international supply chain; korporativna trajnost; mednarodna dobavna veriga; multinational manufacturing company; poročanje o trajnosti dobavne verige; Slovenia; Slovenija; supply chain sustainability reporting; večnacionalno proizvodno podjetje